ANALISIS KENDALA SISWA BERKEBUTUHAN KHUSUS DALAM MENGIKUTI PEMBELAJARAN INKLUSIF DI SEKOLAH DASAR - Abellia; Amir Hamzah; Miftahul Husni; Faisal; Djoko Rohardi Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of inclusive education in regular elementary schools often faces severe challenges due to limited facilities and the absence of special assistant teachers. This study aims to deeply describe the implementation of inclusive learning for Students with Special Needs (ABK) and analyze the various constraints experienced by these students in elementary schools. This research used a qualitative method with a case study approach. Data collection was carried out at SD Negeri 16 Banyuasin 1 through participatory classroom observations, in-depth interviews with the principal, classroom teacher, and parents, as well as documentation study. Data validity was tested using source, technique, and time triangulation. The results revealed that inclusive learning was implemented through full integration in regular classrooms. Without a Special Assistance Teacher (GPK), the classroom teacher independently performed instructional differentiation, such as reducing daily task loads for ABK students, using visual media, and loosening assessment standards into authentic evaluations. However, the learning participation of ABK students is still hindered by two main constraints. Internally, students experience difficulties in understanding materials, short concentration spans, communication barriers, and unstable emotional conditions. Externally, the learning process is severely hindered by the absence of GPK which creates a double burden for teachers, unadaptive methods and facilities, and minimal parental involvement due to low parenting literacy and economic pressure. In conclusion, inclusion policies that merely focus on physical integration in regular classrooms have not been able to optimize ABK's potential without GPK support and intensive communication with families.